Формування і розвиток української історичної лексикології в загальнослов’янському контексті - Прискока, О.В. (Мовознавство, 2018)
У статті йдеться про виникнення та розвиток історичної лексикології української мови в зіставленні з аналогічним процесом у польській та російській мовах. Виявлено кілька схожих етапів їх формування. Автор дійшов висновку, що кожна з них різною мірою пройшла періоди: глос, ранньої лексикографії, етюдів XIX– XX ст., сучасних досліджень на системному рівні. The study of history of particular Slavic languages draws more attention of Slavic
philologists since the middle of XX-th century. A significant number of works regarding
the origin, written record, and function of various lexical sets of words in ancient
manuscripts had formed the branch of philological science named historical lexicology.
Its advances in slavistics are such noticeable that they give ground to ponder on how the
interest in studying history of words, based on ancient manuscripts, had emerged, how the
method of studying the history of particular Slavic languages vocabulary had developed.
The following stages are observed in this report: gloss; lexicographers; essays of XIX —
XX-th centuries; modern works. The establishing of historical lexicology of Ukrainian
language is traced along with similar processes in philology in neighboring countries,
Poland and Russia.